Head, neck, and brain tumor embolization guidelines. (26th April 2012) - Duffis, E Jesus; Gandhi, Chirag D; Prestigiacomo, Charles Joseph; Abruzzo, Todd; Albuquerque, Felipe; Bulsara, Ketan R; Derdeyn, Colin P; Fraser, Justin F; Hirsch, Joshua A; Hussain, Muhammad Shazam; Do, Huy M; Jayaraman, Mahesh V; et al.
Abstract : Background: Management of vascular tumors of the head, neck, and brain is often complex and requires a multidisciplinary approach. Peri-operative embolization of vascular tumors may help to reduce intra-operative bleeding and operative times and have thus become an integral part of the management of these tumors. Advances in catheter and non-catheter based techniques in conjunction with the growing field of neurointerventional surgery is likely to expand the number of peri-operative embolizations performed. The goal of this article is to provide consensus reporting standards and guidelines for embolization treatment of vascular head, neck, and brain tumors. Summary: This article was produced by a writing group comprised of members of the Society of Neurointerventional Surgery. A computerized literature search using the National Library of Medicine database (Pubmed) was conducted for relevant articles published between 1 January 1990 and 31 December 2010. The article summarizes the effectiveness and safety of peri-operative vascular tumor embolization. In addition, this document provides consensus definitions and reporting standards as well as guidelines not intended to represent the standard of care, but rather to provide uniformity in subsequent trials and studies involving embolization of vascular head and neck as well as brain tumors. Conclusions: Peri-operative embolization of vascular head, neck, and brain tumors is an effective and safe adjuvant to surgical resection. Major complications reported in the literature are rare when these procedures are performed by operators with appropriate training and knowledge of the relevant vascular and surgical anatomy. These standards may help to standardize reporting and publication in future studies.